Neonatal Necrotizing Enterocolitis - H. Tjandra (Paediatrica Indonesiana, 1978)
Neonatal Necrotizing Enterocolitis (NEC) is a highly lethal disease of the newborn infant, which has aroused great interest in the past decades. It is characterized by ischemic necrosis of the intestinal wall, frequently leading to perforation and death. Unlike most neonatal emergencies, it is acquired and can be successfully treated without operation in most cases.The etiology is still obscure and is considered to be multifactorial. Intesti11al ischemia, infections, cow's milk, and hyperosmolar feeding are among the important factors associated with the pathogenesis of NEC in the newborn Many other factors are also related to the occurrence of this disease but some of them are still controversial.The general opinion is that requiring a background of mucosal ischemia and damage; the presence of both intestinal bacteria and enteric feedings appear to be of significant etiologic factors. The important pathologic lesion is the mucosal damage and necrosis involving mostly the ileum and colon exdept the duodenum. Perforations usually occur in the ileocecal region where the intestinal wall is extremely thin.